A Comprehensive Review on the Anti-Cancer Effects of Oleuropein - Sabreen Rishmawi; Fatma Haddad; Ghadeer Dokmak; Rafik Karaman (Life, 2022)
In Mediterranean cuisine and culture, olive oil and olive fruits play a significant role. Many people believe that those who consume olive oil and its fruit live longer and have a decreased risk of illness. Olive leaves were used to treat a range of diseases in ancient times, including malaria fever and lower earaches. Although it was not understood at the time what key components were responsible for these effects because they had not yet been discovered, Oleuropein is now recognized as one of the primary elements in immature olive fruits and leaves. Later research was carried out to determine the effects of this molecule, and it was determined that it functions as an antioxidant. Oleuropein consumption has aided in cancer treatment over the years, and this was assumed to be owing to its antioxidant properties. Oleuropein’s effects on cancer, however, go beyond that; it is now known that Oleuropein functions as both an anti-proliferative and an apoptotic promoter in many cancer cells. The kinetics and dosages of Oleuropein and the mechanisms behind its involvement and effects in cancer are explored in this review. Finally, the effects of Oleuropein in combination with anticancer medicines are investigated.